2016
DOI: 10.1177/0267659116651484
|View full text |Cite
|
Sign up to set email alerts
|

Management considerations of massive hemoptysis while on extracorporeal membrane oxygenation

Abstract: Background: Veno-arterial extracorporeal membrane oxygenation (V-A ECMO) is a life-saving procedure in patients with both respiratory and cardiac failure. Bleeding complications are common since patients must be maintained on anticoagulation. Massive hemoptysis is a rare complication of ECMO; however, it may result in death if not managed thoughtfully and expeditiously. Methods: A retrospective chart review was performed of consecutive ECMO patients from 7/2010-8/2014 to identify episodes of massive hemoptysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 10 publications
(21 reference statements)
0
27
0
Order By: Relevance
“…Krecmerova et al [ 10 ] successfully performed massive alveolar lavage with severe alveolar proteinosis under the support of ECMO. Pitcher et al [ 11 ] successfully performed emergency surgery on patients with massive hemoptysis with ECMO support. Natt et al [ 12 ] successfully performed balloon dilatation and tracheal stenting with V-V ECMO support in patients with severe tracheal occlusion after tracheal intubation, and the patient's postoperative dyspnea was significantly restored.…”
Section: Discussionmentioning
confidence: 99%
“…Krecmerova et al [ 10 ] successfully performed massive alveolar lavage with severe alveolar proteinosis under the support of ECMO. Pitcher et al [ 11 ] successfully performed emergency surgery on patients with massive hemoptysis with ECMO support. Natt et al [ 12 ] successfully performed balloon dilatation and tracheal stenting with V-V ECMO support in patients with severe tracheal occlusion after tracheal intubation, and the patient's postoperative dyspnea was significantly restored.…”
Section: Discussionmentioning
confidence: 99%
“…A previous retrospective study reported that complications from massive hemoptysis occurred in 2.5% of patients on ECMO (3). The occurrence of massive hemoptysis in heparinized ECMO patients, although rare, is a serious and potentially lethal complication.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombotic events (clot requiring circuit change, deep vein thrombosis, pump head failure due to clot, or pulmonary embolism) happened at a rate of 53% (16). Pitcher et al highlights how to manage hemoptysis while on ECMO (17). In a retrospective case series, 3 patients on VA-ECMO developed massive hemoptysis (defined as greater than 300 mL of blood in 24 hours) in the setting of antiplatelet therapy or a pulmonary artery catheter placement and were refractory to correction of coagulation, cold saline or epinephrine by bronchoscopy or bronchial blocker placement.…”
Section: Foreign Body Retrievalmentioning
confidence: 99%
“…Bronchoscopy is performed afterwards for removal of clot and bronchial casts. Cryotherapy can help facilitate removal of clot from the lungs (17). Once bleeding stops, anticoagulation is resumed due to thromboembolic risk with careful monitoring of rebleeding.…”
Section: Foreign Body Retrievalmentioning
confidence: 99%